Integration of Disaster Preparedness Materials in Islamic Education (PAI) Subjects at SD Muhammadiyah Insan Kreatif Kembaran Bantul - Hamidi, Nur; Fajri, Chaamid Nur (Program Studi Pendidikan Agama Islam, 2021)
The implementation of the integration of disaster preparedness materials in PAI subjects in SD Muhammadiyah Insan Kreatif Kembaran is an innovation in integrating Islamic religious learning with the context of community needs. The purpose of this research is to reveal the concept of materials for disaster that can be integrated in PAI subjects, their implementation, and the things that support and hinder the integration. This research is a type of field research. The data collection uses interview, observation, and documentation methods. The results of the study explain that: 1) Conceptually, the integration of disaster preparedness materials in PAI subjects is still not mature. 2) From the unfinished concept, the integration of disaster preparedness materials in PAI subjects has not yet been implemented. 3) Supporting factors consist of three factors, namely: experience in integrating disaster preparedness materials with thematic subjects, having many parties to work with, and supporting environmental factors. 4) The inhibiting factors for the integration of disaster preparedness materials in PAI subjects are the change of PAI teachers, the lack of understanding of the DRR program, the lack of socialization from the government about the Disaster Safe Education Unit program, and the lack of information about the integration of disaster preparedness materials in PAI subjects.